CHARACTERIZATION OF MIXED LIGAND COMPLEXES OF Cr(lll) AND Fe(III) WITH PYROGALLOL AND HETEROCYCLIC AMINES - ISLAM , M. SAIDUL; REZA , M. YEAMIN; UDDIN , M. MASIR (Biological Sciences - PJSIR, 2022)
The octahedral mixed ligand complexes of the type K[Cr(PGH)2L2]' K[Cr(PGH)2L'], K[Cr(PGH)2L~} and K[Fe(PGH)2L2]' K[Fe(PGH)p], K[Fe(PHG)2L;]; where PGH = Deprotonated pyrogallol; L = Quinoline (Q), Isoquinoline (IQ), cc-picoline (a-Pic), y-picoline (y-Pic); L' = 2-aminopyridine (2-APY), 3-aminopyridine (3-APY), L" = Pyridine (PY), were prepared in the solid form and characterized on the basis of elemental analysis, conductivity measurements, magnetic measurements, infrared and electronic spectral studies.